The juvenile ECG pattern in adolescent athletes and non-athletes in a national cardiac screening program (BEAT-IT). (15th January 2023) - Abela, Mark; Yamagata, Kentaro; Buttigieg, Lisa; Xuereb, Sara; Bonello, John; Soler, Jeremy Fleri; Camilleri, William; Grech, Neil; Xuereb, Rachel; Sapiano, Karl; Abela, Estelle; Callus, Adrian; et al.
Abstract: Background: Anterior T wave inversion (TWI) is frequent in healthy adolescent individuals (juvenile ECG pattern), normalising after puberty. Its clinical implications are uncertain. Aim: This study assessed a) national prevalence of anterior TWI, b) ST segment morphology, c) proportion of individuals with a juvenile ECG pattern whose ECG normalises and d) factors predicting TWI persistence >16 years. Methods: Adolescents (mean 15y) in Malta were systematically invited to enrol in a cardiac screening program. Subjects completed a health questionnaire and an ECG at their school. Participants with TWI were labelled as TWI in V1 -V2 or extended TWI (V1 -V3 /4 ). The latter were followed at 1 year with a repeat ECG. Those with persistent extended anterior TWI were offered evaluation and surveillance. Results: The prevalence of isolated anterior TWI was 5.0%, commoner in females (6.3%) independent of athletic ability. Extended TWI was commoner in female athletes (4.2%, non-athletes 2.1%). Females often had shallow TWI without overt ST segment abnormalities. Deep TWI and ST segment changes were more frequent in males. Only 0.2% of cases persisted ≥16 years of age. ST segment characteristics were not able to predict T wave normalisation. No events took place during follow up (40 ± 9 months). Conclusion: Anterior TWI is a frequent phenomenon in adolescents, especially in females. Female athletes are also more likely to have extended anterior TWI. Only 0.2% of cases have persistent anterior TWI at 16 years of age. Chest wall anatomy may explain this phenomenon in females. It is uncommon in males, hence why surveillance is more prudent. Highlights: Anterior T wave inversion (ATWI) is a frequent finding in healthy adolescents. Prevalence of isolated ATWI was 5.0%, commoner in females (6.3% vs 3.7%). Extended ATWI were more common in female athletes (4.2%) vs non-athletes (2.1%). Females often had shallow TWI without overt ST segment abnormalities. Deep TWI and ST segment changes were more frequent in males. 0.2% of cases with ATWI persisted at ≥16 year (an unpredictable phenomenon).